2019
DOI: 10.33221/jiki.v9i02.253
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sikap, Dukungan Teman Sesama Wanita Pekerja Seks (WPS) dan Motivasi terhadap Perilaku Pencegahan HIV/AIDS WPS

Abstract: HIV (Human Immunodeficiency Virus) merupakan suatu virus yang menyerang sistem kekebalan tubuh manusia dan melemahkan kemampuan tubuh untuk melawan penyakit yang datang. Tertularnya seseorang dengan HIV ini akan menyebabkan orang tersebut menderita sakit AIDS (Acquired Immunodeficiency Virus). Salah satu kelompok beresiko tertular penyakit ini adalah wanita pekerja seks (WPS) karena perilakunya yang cenderung berhubungan dengan banyak pelanggan. Tujuan penelitian untuk mengetahui pengaruh langsung dan tidak la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…22 The variable which directly affected the HIV/AIDS preventing behavior on the result of hypothesis test was from the same Sexual Worker Women (WPS) friends' support about 22.9% on Sexual Worker Women (WPS) HIV/AIDS preventing behavior. 23 The result of the research showed that teenagers' behavior variable was directly affected by peer friends about 32.563% in preventing HIV/AIDS. This result presented that peer friends' role influenced teenagers' behaviors due to daily socialization at a school environment with friends.…”
Section: Discussionmentioning
confidence: 96%
“…22 The variable which directly affected the HIV/AIDS preventing behavior on the result of hypothesis test was from the same Sexual Worker Women (WPS) friends' support about 22.9% on Sexual Worker Women (WPS) HIV/AIDS preventing behavior. 23 The result of the research showed that teenagers' behavior variable was directly affected by peer friends about 32.563% in preventing HIV/AIDS. This result presented that peer friends' role influenced teenagers' behaviors due to daily socialization at a school environment with friends.…”
Section: Discussionmentioning
confidence: 96%
“…According to research 18 Female sex workers receive support from peers to prevent HIV/AIDS by always being reminded of the Voluntary Counseling and Testing (VCT) schedule, giving each other advice, admonishing each other, and supporting each other. Socially, FSWs infected with HIV often get stigma and discrimination from family, friends, co-workers, and the surrounding community.…”
Section: Discussionmentioning
confidence: 99%
“…Semakin lama seseorang menjalani VCT maka semakin tinggi kualitas hidupnya. 16,17 Hal ini diakibatkan karena semakin banyak konseling dan pengobatan yang dilakukan oleh ODHA. 15 ODHA yang mengikuti VCT, menjalani hidupnya secara positif, adanya stigma negatif dan diskriminasi yang diterima di masyarakat bukan suatu hal untuk menarik diri, bahkan tetap aktif dan produktif dalam menjalani aktivitas sehari-hari.…”
Section: Metodeunclassified